All I Need is the Air that I Breathe - Avora, Emi; Anastasiou, Spyros; Bachlitzanaki, Irini; Batchelor, David J.; Christodoulides, Savvas; Christofilogiannis, Dionisis; Hurth, Dominique; Mallouris, Andreas; Marathaki, Eva; Mina, Anastasia; Münster, Jost; Nottellet, Olivier; et al. (My University, 2021)
‘In its incredible diversity, drawing has been a primary and primal medium for conveying an artist’s vision; it is also the starting point for its development and elaboration. No matter what an artist’s individual treatment of a specific surface for drawing is, what is self-evident, ultimately, is the immediacy of the gesture out of which any kind of drawing emerges. This immediacy of gesture in drawing, and its pronounced utility during a period of crisis, are the focal points of All I Need Is the Air that I Breathe, an exhibition inspired by the song The Air that I Breathe (1972) by the British band The Hollies. In these pandemic times, drawing takes on a new urgency: It goes beyond a mere practice of producing and capturing linear forms on different mediums to serve as a valuable tool in navigating the straits in which the majority of artists have found themselves in recent months. Drawing could be the answer to the existential questions raised in the current social landscape. Through drawing anxiety can be both communicated and alleviated.’